Double trouble: Co‐occurrence of testosterone deficiency and body fatness associated with all‐cause mortality in US men. (20th November 2017) - Lopez, D.S.; Qiu, X.; Advani, S.; Tsilidis, K.K.; Khera, M.; Kim, J.; Morgentaler, A.; Wang, R.; Canfield, S.
Summary: Background: Testosterone deficiency (TD, total testosterone ≤350 ng/dL [12.15 nmol L −1 ]) and obesity epidemic are growing in parallel in the United States. Yet, the sequelae of TD and obesity on the risk of mortality remain unclear. Objective: To investigate whether the co‐occurrence of TD and overall obesity (body mass index ≥30 kg/m 2 ), and abdominal obesity (waist circumference ≥102 cm), is associated with a risk of all‐cause mortality in American men. Design: The data were obtained from the NHANES 1999‐2004 and the Linked Mortality File (December 31, 2011). A total of 948 participants aged ≥20 years old with endogenous sex hormones and adiposity measurements data were included in this study. Results: Over a median of 9.5 years of follow‐up, 142 men died of any cause in this cohort. Multivariable analysis showed a 2.60 fold increased risk of death among men with TD compared with men without TD (Hazard Ratio [HR] = 2.60; 95% confidence interval [CI] = 1.20‐5.80). No evidence for interaction between TD and overall or abdominal obesity with risk of death ( P interaction ≥ .80). However, only after comparing men with TD and abdominal obesity with men without TD and no abdominal obesity, we found a 3.30 fold increased risk of death (HR = 3.30, 95% CI = 1.21‐8.71). Conclusion: Men with co‐occurrence of TD and abdominal obesity have a higher risk of mortality. The effect of co‐occurrence of TD and abdominal obesity should be further explored with a larger and longer follow‐up time study.